Sport and exercise science New Zealand
OBJECTIVES Applied Services ("assessing Athletes") The provision of anthropometric, biomechanical, medical, nutritional, physiological and psychological assessment of athletes, with on-going support as required by coaches and athletes in each of these areas to monitor and evaluate current training and performance. Applied Research ("seeking answers") Finding practical solutions to problems experienced by coaches and performers. Quality Control ("providing excellence") Standardisation of procedures and accreditation of professional providers. Talent Identification (recognising our potential") Identification of potentially elite achievers by the development and implementation of a Talent Identification (TID) Programme. Education ("enhancing knowledge") Provision of current sport science information to athletes and coaches. Professional Development ("ensuring excellence") Provision of on-going experiences for NZ sport scientists to ensure their position at the forefront of advancement in science and technology.